2003
DOI: 10.1046/j.1523-1747.2003.12471.x
|View full text |Cite
|
Sign up to set email alerts
|

Iron and 8-Isoprostane Levels in Acute and Chronic Wounds

Abstract: The purpose of this study was to determine differences in iron and iron protein (ferritin and transferrin) levels in chronic venous ulcers and acute wounds. The deleterious effect of iron in free-radical-induced tissue damage was indirectly examined by assessing 8-isoprostane levels and antioxidant status in wound fluid samples. Wound fluid samples from chronic leg ulcers in nonhealing and healing phases and wound fluid from mastectomy wounds were assayed for ferritin, transferrin, total iron, 8-isoprostane, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
84
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(90 citation statements)
references
References 51 publications
5
84
0
1
Order By: Relevance
“…Studies showed that chronic venous disease typically leads to iron deposition in tissues [1,48], which is in accordance with the present study.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…Studies showed that chronic venous disease typically leads to iron deposition in tissues [1,48], which is in accordance with the present study.…”
supporting
confidence: 93%
“…Bilateral jugular vein stenosis in CCSVI was associated with activation of the cervical and intracranial collateral circles shunting the blood towards the superior vena cava and the azygos venous system, respectively [48]. The activation of these collateral circuits was confirmed by CT venogram in the JVL animal model used by Atkinson et al [3]; in the present study, the rat model was used replacing the original mouse model, the cerebral venous drainage in both species is similar as well as the brain structure with few minor differences [29,44].…”
mentioning
confidence: 99%
“…This contributes to an up to 20-fold higher iron concentration in the lower limbs of CVU patients than in the upper arms of the same patients (25). Iron overload in tissue and wound exudates of CVUs, but not of acute wounds (AWs), was confirmed in 2 independent studies (18,19). In the presence of H 2 O 2 released by macrophages and neutrophils, iron drives the generation of highly toxic hydroxyl radicals (OH • ) via the Fenton reaction.…”
Section: Introductionmentioning
confidence: 92%
“…So far, there is evidence that venous hypertension - caused by venous valve incompetence - results in venous stasis of the lower extremity, low or absent shear stress, and hypoxia, which all trigger endothelial cell activation with "trapping" of monocytes/macrophages and other leukocytes in the microcirculation (13)(14)(15). Activated monocytes/macrophages and other leukocytes transmigrate into the tissue and release high amounts of proinflammatory cytokines (16), proteases (17), and ROS (18,19), which are responsible for the breakdown of the connective tissue and of essential growth factors (20)(21)(22), eventually leading to ulcer formation (1, 2, 9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation